A nation in the red : the government debt crisis and what we can do about it - Holland, Murray (McGraw-Hill Education, 2014)
Our government debt is rising every day. Our population is shifting as more people retire and fewer are able to find work. This title helps you learn: how reckless spending by Congress has created a debt trap; and how Obamacare will negatively affect health care costs and our economy.